The school of hard knocks: Pre-service teachers’ mindset and motivational changes during their practicum (Foro de Educacion, 2020)
The mindset and motivation that teachers demonstrate are likely to influence their students’ mindset and motivation. While mindset and motivation of in-service teachers have been investigated thoroughly, the same cannot be said of pre-service teachers. Pre-service teachers’ mindset and motivation are likely developed during in-class experiences or practicum, the latter seen as the defining experience of pre-service teachers’ preparation. Understanding the changes that pre-service teachers undergo during their practicum experiences in terms of theories of intelligence, teaching efficacy, resilience, and grit is therefore crucial. This study used these constructs as examples of mindsets, self-beliefs, capacities, and personality traits. A cross-sectional design compared American and Canadian pre-practicum versus post-practicum pre-service teachers’ growth mindset and motivation and illustrated that similar effects occur across national contexts through a primarily quantitative questionnaire with open-ended questions. Triangulated statistical and thematic analyses illustrated that post-practicum students were less idealistic about the incremental nature of intelligence and reported higher resilience and a more pragmatic approach to teaching than their pre-practicum peers. The study’s findings extended other studies’ findings illustrating that changes occur specifically in teacher mindset as well as their strategies. Teacher education programs informed by these specific changes can capitalize on the pragmatic shift of teachers’ strategy selection while also coaching them to retain an incremental view of intelligence for their students’ benefit.